PELOTON INTERACTIVE, INC. (PTON): STRATEGIZING CORPORATERESOURCES AND CAPABILITIES - Woodward, Gillian; Peterson, Karli; Erude, Adesuwa; Saeed, Mohammad; Ondracek, James; Carter, Drew; Head, Kate; Nicholson, Garrett; Bertsch, Andy (Program Pascasarjana, Universitas Riau, 2023)
The purpose of the study is to conduct an in-depth analysis of Peloton Interactive, Inc., as well as to evaluate how the corporate resources and capabilities are strategized to gain and maintain a competitive position in the exercise and health industries. Based on an in-depth analysis, recommendations are made to support Peloton’s future presence in the exercise and health industries. Further research may be conducted to generalize findings beyond the current parameters of this study. The study features Peloton and its endeavors to strategize its corporate resources and capabilities in the best interest of its stakeholders. This case study is suitable for undergraduate and graduate business students who want to apply critical thinking, strategic planning tools, and decision-making skills. It features the company’s quest for relevance and competitiveness.